2020
DOI: 10.7759/cureus.9127
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain Among Weightlifting Adolescents and Young Adults

Abstract: Background Weightlifting is a common type of sports training that develops the strength and size of skeletal muscles. Low back pain (LBP) is one of its most common complaints. This sport has become prevalent among adolescents and young adults as they work to enhance their physique and body image. The aim of our study is to explore the nature and cause of LBP in weightlifting adolescents and young adults in an aim of extrapolating proper preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…Furthermore, it was reported that working with the trunk in bent and twisted positions for more than two hours/day may expose the athlete to a low back injury and should be considered as a risk factor for low back pain. Also, excessive weights puts the back in a compromising position that may lead to injury [15,16]. Moreover, Coenen et al determined that the cumulative low back loads may be a significant risk factor for low back pain [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was reported that working with the trunk in bent and twisted positions for more than two hours/day may expose the athlete to a low back injury and should be considered as a risk factor for low back pain. Also, excessive weights puts the back in a compromising position that may lead to injury [15,16]. Moreover, Coenen et al determined that the cumulative low back loads may be a significant risk factor for low back pain [17].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review, Heneweer et al concluded that heavy workload and the accumulation of loads or the frequency of lifts were moderate to strong risk factors for low back pain [18]. Also, Fares et al reported performing improper techniques as a risk factor for low back injuries [16]. While irreversible changes in the lumbar vertebra without symptoms were reported in children and adolescents undergoing resistance training [19].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, athletes may suffer injuries such as back pain if they do not choose the correct weight and have proper form [1,2]. Particularly, weightlifting training in young athletes can damage the growth plate and should be performed with extreme caution [3].…”
Section: Introductionmentioning
confidence: 99%
“…Low back pain (LBP) is one of the most common weightlifting complaints, with incidence rates ≥ 40%, caused by lumbar disc degeneration and herniation, which can interfere with not only sports activities but also social life [2]. Although few studies have investigated whether weightlifting training during the growth period is associated with future lumbar disc degeneration and LBP, it is important to note that spinal abnormalities that develop at a young age not only cause LBP at that time, but also increase the risk of recurrence of LBP in adulthood [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the kind of physical activity practiced by a costalero, a comparative analysis is made with power lifting [ 7 , 8 , 9 ]. The aim of weightlifting is to lift a maximum weight in a one-time repeat [ 10 , 11 ], whereas the costalero lifts a lower weight for a longer period of time.…”
Section: Introductionmentioning
confidence: 99%